The Measures of Cultivating Students' Mathematics Application Ability in College Mathematics Teaching - Wu, Jie (Journal of Theory and Practice of Social Science, 2024)
Under the background of the new situation, the comprehensive ability of advocating quality-oriented education and talents cultivation, puts forward higher requirements on college students, the mathematics as a compulsory course in university, its status is self-evident, it can effectively promote students' thinking ability, innovation ability, the progress of the ability to solve the problem, then, still need professional teachers attaches great importance to the application ability training, as education the main line, To improve the traditional teaching malpractice, create a good teaching environment. This paper takes mathematics application ability as the theme, discusses the existing situation and concrete solutions, hoping to provide opinions and suggestions for the education industry.